Desquamative alveolar disease (desquamative interstitial pneumonia): case report. Issue 2 (March 1969) - Cruz, Edgardo; Rodriguez, Jaime; Lisboa, Carmen; Ferretti, Ricardo
Abstract : Desquamative interstitial pneumonia is a disease characterized by massive alveolar cell proliferation and desquamation with sparse interstitial involvement. The reported case shows an unusually widespread radiographic reticulo-nodular image and abundant alveolar cells in the sputum. Functional studies reveal the expected diffusion defect with practically normal mechanical properties of the lung, in contrast with interstitial fibrosing lung diseases. On the basis of the pathological findings, especially the behaviour of alveolar cells, the individuality of this disease is discussed. We think that it is different from other diseases classed as varieties of a single disease or as different entities under the names of primary interstitial fibrosis or chronic fibrosing alveolitis.